Cutting bone with drills, burs, lasers and piezotomes: A comprehensive systematic review and recommendations for the clinician - Angelo Troedhan; Ziad Tarek Mahmoud; Marcel Wainwright; Mohamed Moataz Khamis (International Journal of Oral and Craniofacial Science - Peertechz Publications, 2017)
Background: New tools for bone-cutting were introduced to oral and maxillofacial surgery in the last decade, such as lasers and piezotomes. Purpose: to evaluate most recent evidence, when surgical procedures performed with drills or burs are compared with laser- and/or piezotome-surgical procedures in experimental and clinical studies and to assess possible advantages of their use in daily practice. Methods: a systematic search of various medical databases with specific keywords was performed, excluding studies published before 2006 for their possible invalidity by technological progress. Systematic reviews were assigned to Group 1, experimental studies ex vivo to Group 2, in vivo to Group3 and clinical studies to Group 4. All studies in each of the groups 2 - 4 were appraised regarding their evidence, starting with a value of 0 for no evidence of advantages of lasers and/or piezotomes compared to rotary instruments, 1 for moderate evidence with verifi ed clinical impact and 2 for strong evidence and signifi cant clinical impact and statistically processed for their Evidence Value (EV) in each group and their Overall mean Evidence Value (OmEV). Results: 129 studies were fi nally included for evaluation. Two systematic reviews concluded lack of evidence for lasers to be advantageous over burs/drills. Nine reviews for piezotomes reveal strong evidence piezotome-surgery to signifi cantly reduce morbidity and to enhance soft-tissue preservation. Comparative experimental and clinical studies of burs/drills vs lasers revealed a low EV in Group 2 (EV:0,8), Group 3 (EV:0,5) and Group 4 (EV:0,5) with an OmEV of 0,6. Comparative studies burs/drills vs piezotomes resulted in a signifi cant EV in all groups (Group 2: 1,4, Group 3: 1,3, Group 4: 1,59) with an OmEV of 1,4. Conclusions: the results suggest too little evidence to establish lasers as an alternative to rotary instruments. Piezotomes seem to defi ne a possible new gold-standard in bone cutting due to their improved bone-healing, almost bone-lossless and precise osteotomy design, precise depth-control, softtissue protection as well as reduced intrasurgical and post-surgical morbidity.